Functional factors that are important correlates to physical activity in people with multiple sclerosis: a pilot study. Issue 20 (25th September 2018) - Ketelhut, Nathaniel B; Kindred, John H; Pimentel, Richard E; Hess, Ann M; Tracy, Brian L; Reiser, Raoul F; Rudroff, Thorsten
ABSTRACT: Purpose: Identify functional factors that are important correlates to physical activity levels among people with multiple sclerosis. Methods: A total of eight functional tests were conducted and physical activity was objectively measured (Actigraph GT3X accelerometer) for one week in 34 people with multiple sclerosis. A corrected Akaike Information Criterion analysis was performed to identify the strongest correlates with moderate-to-vigorous physical activity, total activity and sedentary time. Results: The multiple regression analysis converged on a model for moderate-to-vigorous physical activity ( R 2  = 0.31, F  = 6.97, p=  0.003) that included total strength of the less-affected leg (partial r =  0.46, p =  0.007) and average peg test performance (partial r  = −0.30, p =  0.087). The model for total activity ( R 2  = 0.40, F  = 10.51, p <  0.001) included five times sit-to-stand performance (partial r = −0.44, p =  0.010) and total strength of the less-affected leg (partial r =  0.31, p =  0.077). The model for sedentary time ( R 2 =0.22, F  = 9.23, p =  0.005) only included total strength of the more affected leg ( r = −0.47, p =  0.005). Conclusion: These results suggest that leg strength, manual dexterity and the ability to perform functional tasks may be important correlates with physical activity levels in people with multiple sclerosis. The findings of this pilot study can inform future investigations aiming to increase physical activity levels or develop improved rehabilitation protocols for people with multiple sclerosis. Implications for Rehabilitation: Physical activity is an effective means of improving the symptoms associated with multiple sclerosis. Participation in physical activity by people with multiple sclerosis may be affected by functional factors such as leg strength, manual dexterity and the ability to rise from a seated position. Bilateral leg strength differences should be assessed and addressed in people with multiple sclerosis.